Feminist Identity, Attitudes Toward Feminist Prototypes, and Willingness to Intervene in Everyday Sexist Events. (September 2018) - Weis, Alexandra S.; Redford, Liz; Zucker, Alyssa N.; Ratliff, Kate A.
Many women eschew the feminist label despite believing in gender equality. In order to effectively promote feminist change, it is important to understand the factors involved in feminist attitudes, identification, and behavior. In the present research, we helped clarify the relations among these factors. In a survey of 428 U.S. women, we found that participants with stronger attitudes toward gender equality and more favorable explicit and implicit attitudes toward feminist prototypes were more likely to claim a feminist label. And those who did so reported greater willingness to intervene when confronted with everyday sexist behavior, particularly if they perceived that they personally were vulnerable to the effects of sexism. We suggest that improving attitudes toward feminist prototypes may help promote feminist identification, and informing women about the pervasiveness of sexism, including their personal vulnerability, may promote willingness to act after the feminist label has been adopted. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://journals.sagepub.com/page/pwq/suppl/index